New interchange : - Richards, Jack C (Cambridge University Press, 1998)
New Interchange is a multi-level series for adult and young-adult learners of English from the beginning to the high-intermediate level. The Workbook has six-page units that follow the same sequence as the Student's Book. It has interesting grammar, vocabulary, and writing activities, appropriate for classwork or homework